The Dynamics of Government Policies on Islamic Education in Indonesia from the Old Order to the Reform Era - Ritonga, Rasyd Ripai; Noviani, Dwi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze the development and dynamics of government policies toward Islamic education in Indonesia from the Old Order and New Order periods to the Reform era. Each period demonstrates distinct policy directions shaped by the political, social, and ideological context of its time. Using a library research method, this study examines primary and secondary sources, including books, legal regulations, and scientific articles related to the history of Islamic education. The findings reveal that during the Old Order period, government policies focused on recognizing and establishing the Ministry of Religious Affairs as the institution responsible for managing Islamic education. In the New Order era, policies shifted toward integrating madrasahs into the national education system, exemplified by the 1975 Joint Decree of Three Ministers. Meanwhile, in the Reform era, the government broadened its recognition of Islamic educational institutions—such as pesantren and majelis taklim—through Law No. 20 of 2003 on the National Education System. Overall, government policies across these periods demonstrate continuity and positive transformation in the recognition, development, and legitimization of Islamic education in Indonesia. Keywords: Government Policy, Islamic Education, Old Order, New Order, Reform Era